Nutrient Balance at Integrated Nutrient Management on Lowland Rice Which is Dominated by 1:1 Clay Mineral for High Potential Rice Yields - Kasno, Antonius (UNIVERSITY OF LAMPUNG, 2010)
Nutrient Balance at Integrated Nutrient Management on Lowland Rice Which is Dominated by 1:1 Clay Mineral for High Potential Rice Yields (A Kasno): The curve of the most recent production period of the intensification lowland rice was stating a levelling off. In the effort to increase the rice production, an improvement on intensification quality using a balance fertilizing concept was determined. The objective of this research was to study the nitrogen, phosphorus and potassium nutrient balance among the integrated nutrient management. The field experiment was conducted in Margodadi and Mulyosari, Metro, Lampung, in dry season 2006. A randomized Complete Block Design was applied with ten treatments and three replications. The treatments combined of inorganic and organic fertilizers. Phosphorus and potassium dosages and proportions were determined based on the previous research held in 2005, it were 100 kg SP-36 ha-1 and 80 kg KCl ha-1 in Mulyosari, and 130 kg SP-36 ha-1 and 120 kg KCl ha-1 in Margodadi. At the beginning, 100 kg urea was added. The crop’s need of nitrogen was monitored using the Leaf Color Chart every 7-10 days, starting from the 21st days after planting, up to the phase panical inisiation. Total urea fertilizer added was 300 kg ha-1. Organic matters consisting of 5 Mg ha-1 rice straw and 2 Mg ha-1 cow manure were added. Ammonium sulphate was added to provide 10 kg S ha-1 and by 5 minutes dying the seedlings on 0,05% ZnSO4 solution before planting was intended to provide Zn nutrient. Micro nutrient Cu was provided by adding 5 kg ha-1 CuSO4. The plot size was 5m x 5m, and Hybride Rice, PHB 71, was used as the plant indicator. Observation was focused on the weight of dry straw and yield and on analysing the nutrient content of straw and grain yield. The result showed that the weight of the yield increased from 7.44 to 7.93 Mg ha-1 by adding Cu in Mulyosari. The total production of Hybride PHB 71 in the NPK treatment based on the Margodadi and Mulyosari nutrient status were 7.44 and 7.00 Mg ha-1, respectively. Adding KCl 120 kg ha-1 in Margodadi and 80 kg ha-1 in Mulyosari was equal to the incorporating 5 Mg ha-1 rice straw in acheiving the same rate of the weight of the yield. Incorporating straw 5 Mg ha-1 increased the nutrients content of harvested straw/grain: N from 105 to 123 kg ha-1, P from 26 to 34 kg ha-1, and K from 106 to 114 kg ha-1 in Margodadi, while in Mulyosari increasing N from 114 to 128 kg ha-1, P from 26 to 34 kg ha-1, and K from 71 to 87 kg ha-1. Nutrient balance in Margodadi was in the range of -12 to 68 kg ha-1, -16 to -7 kg ha-1, and -68 to -5 ka ha-1 for N, P, and K, respectively, while in Mulyosari was in the range of -23 to 67 kg ha-1, -19 to -10 kg ha-1 and -60 to -28 kg ha-1 for N, P, and K, respectively. Incorporating rice straw to the rice field was able to improve the balance of N, P, and K nutrients in the rice field.